Mycoplasma pneumoniae-Induced Rash and Mucositis: A Management Dilemma - S. Abreu, Margarida (2023)
Mycoplasma pneumoniae induced rash and mucositis is a recently acknowledged clinical entity; therefore, the effectiveness and utility of therapeutic options are still under investigation. This case report aims to highlight the clinical characteristics of this disease and share a report on its management. Herein is reported a previously healthy 15-year-old male admitted with a high fever, severe oral and ocular mucositis, and scattered bullous lesions with an erythematous halo. The epidemiological context was irrelevant, and laboratory tests revealed elevated inflammatory markers. The patient received complete supportive care and intravenous immunoglobulin; however, there was no clinical or laboratory response. After the etiological investigation supported a Mycoplasma pneumoniae infection, treatment with azithromycin and systemic corticotherapy started, which led to favorable outcomes. He was discharged after 24 days with no sequelae. When Mycoplasma pneumoniae-induced rash and mucositis is suspected, extensive testing for mycoplasma infection should be granted and cautiously interpreted. Since disease management lacks robust scientific evidence, case reporting is significantly needed.